The Recovery of a Canadian Tradition in Higher Education - Bissell, Claude T. (Canadian Journal of Higher Education, 1977)
Amid the present public indifference to higher education, the appearance of the Symons report was welcome, since it drew attention to national issues. Although it is important to examine the curriculum from the point of view of Canadian content, a separation of Canadian content from a particular discipline may encourage provincialism and didactism. It is more important for universities to examine the role they have played and are playing in the national life. I suggest the establishment of a group of interdisciplinary seminars at various universities across the country, staffed by existing faculty and post-doctoral students, and concerned with the examination of crucial Canadian problems.